ANALISIS NILAI TAMBAH NATRIUM LAURAT DAN KALIUM PALMITAT SEBAGAI BAHAN BAKU FOAMING AGENT PEMADAM KEBAKARAN - Purwo Subekti; Erliza Hambali; Ani Suryani; Prayoga Suryadarma; Bambang Hero Saharjo (Department of Agroindustrial Technology, Bogor Agricultural University, 2020)
The calculation of the added value of using a foaming agent based on sodium lauric and potassium palmitate for palm oil as a peatland fire suppression needs to be studied. This was to determine prospects for further development because it is predicted that peatland fires will continue to recur every year during the dry season. The Hayami method used to analyze the added value of sodium lauric and potassium palmitate as the primary raw materials for foaming agents. The results showed that the production of foaming agents for peatland firefighting applications made from sodium laurate and potassium palmitate of palm oil provided added value with positive criteria, i.e. the ratio of value-added criteria was 80.87% (> 0). In addition to that, the business also provided high-profit categories because the added value category ratio was 80.87% (> 40%). From the analysis of remuneration, it was produced that the foaming agent production business was a capital-intensive since the contribution of the labour income value was 0.89%, other expenses contributed 3.73% and the profit from the entrepreneur as the owner capital of 95.37% which was the largest contribution in providing profit margins. However, the development of a foaming agent production business based on palm oil fatty acids will add new jobs and create new economic impacts in the area of the business locations as well as to increase the amount of palm oil derivative products. Keywords: added value, foaming agent, sodium lauric, potassium palmitate, palm oil